Distinct Oncogenic Transcriptomes in Human Mammary Epithelial Cells Infected With Cytomegalovirus - Haidar Ahmad, Sandy; Pasquereau, Sébastien; El Baba, Ranim; Nehme, Zeina; Lewandowski, Clara; Herbein, Georges (Frontiers in Immunology, 2021)
Human cytomegalovirus is being recognized as a potential oncovirus beside its oncomodulation role. We previously isolated two clinical isolates, HCMV-DB (KT959235) and HCMV-BL (MW980585), which in primary human mammary epithelial cells promoted oncogenic molecular pathways, established anchorage-independent growth in vitro, and produced tumorigenicity in mice models, therefore named high-risk oncogenic strains. In contrast, other clinical HCMV strains such as HCMV-FS, KM, and SC did not trigger such traits, therefore named low-risk oncogenic strains. In this study, we compared high-risk oncogenic HCMV-DB and BL strains (high-risk) with low-risk oncogenic strains HCMV-FS, KM, and SC (low-risk) additionally to the prototypic HCMV-TB40/E, knowing that all strains infect HMECs in vitro. Numerous pro-oncogenic features including enhanced expression of oncogenes, cell survival, proliferation, and epithelial-mesenchymal transition genes were observed with HCMV-BL. In vitro, mammosphere formation was observed only in high-risk strains. HCMV-TB40/E showed an intermediate transcriptome landscape with limited mammosphere formation. Since we observed that Ki67 gene expression allows us to discriminate between high and low-risk HCMV strains in vitro, we further tested its expression in vivo. Among HCMV-positive breast cancer biopsies, we only detected high expression of the Ki67 gene in basal tumors which may correspond to the presence of high-risk HCMV strains within tumors. Altogether, the transcriptome of HMECs infected with HCMV clinical isolates displays an “oncogenic gradient” where high-risk strains specifically induce a prooncogenic environment which might participate in breast cancer development.